Karakter Guru dan Siswa Perspektif Imam Al-Ghozali - Rizki Pauzi (Islamuna: Jurnal Studi Keislaman, 2025)
Teachers must possess character traits that can serve as role models for students. However, in reality, there are still teachers who do not have good character traits that students can emulate. Students, as the future generation of the nation and the foundation of the success of a citizen, must have good personality traits for their success one day. Moreover, the teachings of Islam require its followers to learn, as education is a matter of great importance and value. The study aims to understand the character of teachers according to Imam Al-Ghazali, the character of students according to Imam Al-Ghazali, and the relevance between the character of teachers and students according to Imam Al-Ghazali. This research employs a literature study method, which involves collecting data done by compiling data from the thoughts of Imam Al-Ghazali focused on the book Ihya Ulumiddin and Ayuhal Walad. The research results show that according to Imam Al-Ghazali, education is a process of acquiring happiness in this world and the hereafter, contentment, reliance on God, humility, love for others, honesty, politeness, generosity, and not being envious or arrogant. These qualities align closely with Islamic education in developing students' characters. According to Imam Al-Ghazali in the book Ayuuhal Walad, the character of both teachers and students should aim at creating individuals who are devoted worshippers, knowledgeable in both religious and general sciences, socially sensitive, reliant on God, obedient to their teachers and the teachings of Allah, compassionate, humble, not arrogant, and free from envy, while also being good citizens who engage in beneficial deeds for all humanity. The character of the teacher has a greater influence on the child than their knowledge and intelligence.